An Introduction to Multiphoton Ionization and Study of Ionization Rate of Hydrogen Atom - Shrestha, N.; Nakarmi, J. J.; Jha, L. N. (Himalayan Physics, 2012)
We have discussed the problems of non linear interaction between electromagnetic radiations with atoms from semi-classical point of view. Time dependent Schrödinger equation for single electron system is solved by using perturbative technique to obtain transition probability. Higher order perturbation is also discussed which is used in multiple processes, in which two or more quanta are emitted instead of a single photon. The theory is based on assumption that the perturbation is small. From this transition probability ionization rate and absorption cross-section of hydrogen atom is calculated. Its variation with photon energy and field strength is analyzed which agrees very well with experimental observations. The Himalayan Physics Vol. 3, No. 3 2012 Page : 40-43